Dampak Lingkungan Bermain Pada Perkembangan Sosial Anak Usia Sekolah di Perumnas 1 Waena Kota Jayapura - Putri, Andrea Gafiria Permata; Rahmawati, Rimba; Zulihi, Zulihi; Yusuf, Muhamad; Watora, Ibrahim; Nawir , M. Syukri (Jayapangus Press, 2025)
Significant changes in children’s play behavior caused by the dominance of digital devices and online games have limited access to physical play. This condition raises concerns about the decline of direct social interactions and opportunities for developing social skills. This study aims to explore the impact of the play environment (particularly technology) on children’s social development and to examine the influence of technology use in the play environment on children’s learning interest in the Perumnas I Waena area of Jayapura City. This research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. Data were analyzed using a flow model. Findings: In Perumnas I Waena, children’s play comfort is influenced by physical, psychological, and social aspects. Although large playgrounds are available, external factors such as stray dogs reduce the sense of safety. Environmental management, adult supervision, and the involvement of parents and the community are needed. Social interaction during play serves as a foundation for children’s social, emotional, and cognitive development. Learning motivation is influenced by the environment, enjoyable learning methods, and the integration of technology. Motivation arises from both intrinsic and extrinsic factors, highlighting the importance of adults in balancing technology use with social interaction. The physical environment strengthens social skills and cooperation, while the digital environment fosters creativity, strategy, and technological skills. A balanced combination of traditional and digital play is required to ensure children’s optimal development.